The impact of temperature on the shear bond strength of conventional multi-step and self-adhesive orthodontic adhesive systems: an in-vitro study - Grėtė Kazlauskaitė; Rytis Vaitiekūnas; Kristina Lopatienė; Audrius Jutas; Benedikta Palesik; Dalia Smailienė (BMC Oral Health)
Abstract Background A recurring issue during orthodontic treatment is the detachment of brackets from the tooth surface, which proves problematic for both the patient and the orthodontist. This study aimed to evaluate the impact of various temperatures on the shear bond strength of metal molar tubes, using conventional multi-step and self-adhesive orthodontic adhesive systems. Methods A total of 112 extracted human molars were randomly divided into eight groups (n = 14) for bonding tubes with two orthodontic adhesive systems (Transbond XT and GC Ortho Connect) at different temperatures: refrigeration temperature (4 °C), room temperature (20 °C), human body temperature (37 °C), and high temperature (55 °C). The shear bond strength (SBS) test was conducted using a universal testing machine set to a crosshead speed of 0.5 mm/min. The adhesive remnant index (ARI) was used to evaluate the amount of adhesive remnants on the molar surfaces. ARI scores were assessed under Carl Zeiss Stemi 2000-CS stereomicroscope with image recording camera AxioCam Mrc5 at ×10 magnification. The data were analyzed using Student’s t-test, parametric analysis of variance (ANOVA), the intra-class correlation coefficient (ICC), the Kruskal-Wallis test, and the chi-square test. Results Higher mean SBS values were obtained with Transbond XT compared to GC Ortho Connect resin; however, the difference was not statistically significant (p > 0.05). The SBS results were lowest at 20 °C and highest at 55 °C in the Transbond XT group, and lowest at 37 °C and highest at 20 °C in the GC Ortho Connect group with no statistically significant difference (p > 0.05). The distribution of the ARI scores between the two materials showed a statistically significant difference (p = 0.002), with higher ARI scores found in the Transbond XT group. Conclusions Pre-heating orthodontic adhesives prior to bonding does not affect the shear bond strength.